THE IMPACT OF THE CASEL MODEL WITH SIMULATION ON FIFTH GRADERS' LEARNING OUTCOMES IN GOTONG ROYONG - Indah Dewi Eka Sari; Novia Rahma Rista Utami; Arum Dwi Rahmawati (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2025)
This study explores the impact of using the CASEL learning model with simulation methods on fifth graders' understanding of Pancasila Education, focusing on gotong royong a cultural value stressing cooperation and tolerance. This value is essential for developing students’ social-emotional and cognitive competencies. To ensure both groups started equally, a balance test using daily repeat scores was conducted before treatment. Learning outcomes were then measured with a posttest and compared using an independent t-test. Results showed that students using the CASEL model with simulations achieved better learning outcomes than those taught with traditional methods. Not only did their conceptual knowledge improve, but their social-emotional competencies also increased significantly when these elements were combined. Therefore, the CASEL learning model with simulation presents an effective alternative strategy to enhance the quality of Pancasila Education. It offers teachers a practical approach to design interactive and collaborative learning experiences. Additionally, this model supports schools in providing adequate facilities needed for effective simulations, helping create a dynamic learning environment that fosters both cognitive and social-emotional growth in students. Keywords: CASEL learning model, simulation method, learning outcomes